Guide to network security - Whitman, Michael E.; Mattord, Herbert J.; Mackey, David; Green, Andrew (Course Technology, Cengage Learning, 2013)
This title provides a review of the network security field, including essential terminology, the history of the discipline, and practical techniques to manage implementation of network security solutions.